Distance-dependent aposematism and camouflage in the cinnabar moth caterpillar (Tyria jacobaeae, Erebidae). Issue 2 (21st February 2018) - Barnett, James B.; Cuthill, Innes C.; Scott-Samuel, Nicholas E.
Abstract : Defended prey often use distinctive, conspicuous, colours to advertise their unprofitability to potential predators (aposematism). These warning signals are frequently made up of salient, high contrast, stripes which have been hypothesized to increase the speed and accuracy of predator avoidance learning. Limitations in predator visual acuity, however, mean that these patterns cannot be resolved when viewed from a distance, and adjacent patches of colour will blend together (pattern blending). We investigated how saliency changes at different viewing distances in the toxic and brightly coloured cinnabar moth caterpillar ( Tyria jacobaeae ). We found that although the caterpillars' orange-and-black stripes are highly salient at close range, when viewed from a distance the colours blend together to match closely those of the background. Cinnabar caterpillars therefore produce a distance-dependent signal combining salient aposematism with targeted background matching camouflage, without necessarily compromising the size or saturation of their aposematic signal.